2019
DOI: 10.1111/jipb.12811
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of folate QTLs using a segregated population in maize

Abstract: As essential B vitamin for humans, folates accumulation in edible parts of crops, such as maize kernels, is of great importance for human health. But its breeding is always limited by the prohibitive cost of folate profiling. The molecular breeding is a more executable and efficient way for folate fortification, but is limited by the molecular knowledge of folate regulation. Here we report the genetic mapping of folate quantitative trait loci (QTLs) using a segregated population crossed by two maize lines, one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 56 publications
3
25
0
Order By: Relevance
“…In this investigation, a genome-wide association study (GWAS) was conducted using a maize association panel containing hundreds of maize inbred lines genotyped by more than 1 million genome-wide single nucleotide polymorphisms (SNPs) 26,27 . We showed that ZmCTM (catalysis of 5-M-THF to MeFox) maps to a previously described quantitative trait locus 28 and encodes a protein that catalyses 5-M-THF to MeFox. The natural A-to-G variation explained 27.6% of the phenotypic variation, and led to a natural asparagine (Asn, N)-to-glycine (Gly, G) substitution in ZmCTM, which enhances its enzymatic activity.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In this investigation, a genome-wide association study (GWAS) was conducted using a maize association panel containing hundreds of maize inbred lines genotyped by more than 1 million genome-wide single nucleotide polymorphisms (SNPs) 26,27 . We showed that ZmCTM (catalysis of 5-M-THF to MeFox) maps to a previously described quantitative trait locus 28 and encodes a protein that catalyses 5-M-THF to MeFox. The natural A-to-G variation explained 27.6% of the phenotypic variation, and led to a natural asparagine (Asn, N)-to-glycine (Gly, G) substitution in ZmCTM, which enhances its enzymatic activity.…”
Section: Introductionmentioning
confidence: 86%
“…A commercial collection of 47 fresh corn hybrids were collected from Shanghai, Guangdong, Beijing, and Sichuan (all in China) and grown in in Hebei (China) in 2020. Field experiments followed the procedures described previously 40 . For the 143 inbred lines, one row was planted for each inbred line and at least three ears in each row were selfpollinated and harvested for folate profiling of mature seeds (Supplementary Result 1).…”
Section: Plant Materials and Field Trialsmentioning
confidence: 99%
“…Folates are quantitative or polygenic traits typically controlled by several small effect QTLs. However, two major effect QTLs namely, q5−F−THFa and q5−F−THFb, explaining 26.7 and 14.9% of the folate variation were identified in maize (Guo et al, 2019) on chromosome 5 by whole−exome sequencing and F 3 kernel−folate profiling. A unique correlation between the folate and the expression of the conserved genes of folate biosynthesis and metabolism was reported in the kernels of maize (Lian et al, 2015).…”
Section: (C) Maizementioning
confidence: 99%
“…The SWI/SNF (SWItch/Sucrose Non‐Fermentable) chromatin remodeling factor deficient in DNA methylation 1 (DDM1) has been demonstrated to play key roles in mediating all three contexts of DNA methylation in parallel with the RNA‐directed DNA methylation (RdDM) pathway in Arabidopsis (Zemach et al ). However, in maize, DDM1 is newly identified to regulate the formation of mCHH islands via the RdDM pathway, highlighting that the machineries of DNA methylation are evolutionarily diverged in different species (Long et al ). This mechanism was also revealed in another independent study (Fu et al ).…”
mentioning
confidence: 99%
“…The genes have the potential to be used as molecular markers in breeding of salt‐tolerant maize cultivars in the future. Guo et al () used the quantitative trait loci (QTL) mapping strategy to explore the genes associate with folate content in mature kernels. Two major folate QTL on chromosome 5 were mapped which contributed 41.6% of the phenotypic variation of 5‐formyltetrahydrofolate, the most abundant storage form among folate derivatives, which is of great importance for human health.…”
mentioning
confidence: 99%